Using Mobile Devices in Teaching Large University Classes: How Does It Affect Exam Success? - Feraco, Tommaso; Casali, Nicole; Tortora, Carla; Dal Bon, Cecilia; Accarrino, Donatella; Meneghetti, Chiara (Frontiers in Psychology, 2020)
The aim of this study was to examine the role of mobile devices in teaching to improve Italian university students’ academic outcomes. In Italian universities it is not uncommon to conduct lessons for large numbers of students. Mobile devices can be useful tools for conveying content, with a potential impact on academic outcomes. This study involved a total of 294 undergraduates taking a course on the psychology of personality and individual differences at Padova University’s School of Psychology. The course involved lessons in the classroom, which included answering quizzes (quiz activities), and out-of-class activities, such as preparing reports and laboratory experiences (out-of-class activities). Quizzes were administered using an advanced mobile technology. Data were collected on the motivational beliefs (theory of intelligence), and self-regulated learning strategies of students voluntarily completing the online questionnaires. The results of linear models showed that using the quiz activities positively affected performance in final exams (involving closed and open questions). The same was true for the out-of-class activities. Motivation and strategy scores correlated moderately with out-of-class activities but not with quiz activities. These results offer insight on the use of technology during lessons and other course-related activities to promote academic achievement.